Make in India – A Prospect of Development for Micro, Small and Medium Enterprises - RN, Balamurugan; J, Dinesh Babu; Neerackal, Jithin J Neerackal (Journal of Contemporary Research in Management (JCRM), 2017)
Abstract The role played by the Micro, Small and Medium Enterprises (MSMEs) in the economic landscape of the country is worth appreciating. With the announcement of Make in India Campaign by our Prime minister Shri. Narendra Modi and its gaining strength and popularity, there is definitely an advantage and scope of growth for MSME sector which already constitutes a major share (45 %) of the Indian manufacturing sector.(SMEs Role in India’s manufacturing Sector, India Brand Equity Foundation). MSMEs can be the backbone for high growth businesses with both domestic and foreign companies investing in the ‘Make in India’ initiative. ‘Make in India with zero defect and zero effect’, is a significant opportunity. The new wave MSME should enable the development of a business eco system that enables and continuously support business that are gearing to deliver the right product, the right quality, the right solution and the right service at a competitive price, both in domestic and international markets. This article tries to understand the benefits of Make in India Initiative on the MSMEs and the supports offered by the government towards enhancing the growth in this sector. Keywords Cluster development program, skill development, budget allocation, collateral free credit, subsidy, credit linked capital subsidy, technology centers, technology up gradation, total quality management, lean manufacturing